Matrizes de gomas regionais para o encapsulamento do óleo essencial de Lippia Sidoides - Oliveira, Erick Falcão de (2012)
Aiming to preserve the properties and optimize the encapsulation of the Lippia sidoides essential oil (LSEO), this work reports on the preparation of chitosan-gum nanoparticles loaded with LSEO by spray-drying, using gums extracted from native trees of northeast of Brazil. The gums used were extracted from exudates of Anacardium Occidentale tree (Cashew gum), Sterculia striata trees (Chichá gum) and Anadenanthera macrocarpa trees (Angico gum). Samples were characterized by FTIR and UV/VIS spectroscopy, particle size and zeta potential, thermal analysis (TGA/DSC) and gas chromatography (GC-MS). The FTIR spectrum showed the main bands of chitosan and gums, in 1550 and 1647 cm-1. Particle sizes ranged from 17 nm to 800 nm, where the angico gum matrix presented the smallest sizes and cashew gum matrix the larger sizes. The zeta potential varied from -40 mV +30 mV, where chichá gum matrix presented the biggest variation. Thermal analysis showed the events of mass loss for the samples, where up to 200° C there are a maximum of 20% mass lost compared to the initial mass. The encapsulation of LSEO ranged between 6 and 16%, where the cashew gum and chichá gum matrixes presented the highest values. Cashew gum samples showed good encapsulation stability after 12 months, where the encapsulated oil content has not changed. The encapsulated oil did not present significant difference in its composition to the initial oil, encapsulating the key components. The release of LSEO from the matrixes was relatively slow, where between 60 and 100% of the oil was released in 48 hours. The kinetic study of LSEO release indicated that the release followed the Higuchi model, with the release by the samples varying between fickians and non-fickians phenomena.